Genetic admixture and language shift in the medieval Volga-Oka interfluve - Peltola Sanni; Majander Kerttu; Makarov Nikolaj; Dobrovolskaya Maria; Nordqvist Kerkko; Salmela Elina; Onkamo Päivi (CELL PRESS, 2026)
The Volga-Oka interfluve in northwestern Russia has an intriguing history of population influx and language shift during the Common Era. Today, most inhabitants of the region speak Russian, but until medieval times, northwestern Russia was inhabited by Uralic-speaking peoples.1-3A gradual shift to Slavic languages started in the second half of the first millennium with the expansion of Slavic tribes, which led to the foundation of the Kievan Rus' state in the late 9th century CE. The medieval Rus' was multicultural and multilingual-historical records suggest that its northern regions comprised Slavic and Uralic peoples ruled by Scandinavian set-tlers.4-6 In the 10th-11th centuries, the introduction of Christianity and Cyrillic literature raised the prestige sta-tus of Slavic, driving a language shift from Uralic to Slavic.3 This eventually led to the disappearance of the Uralic languages from northwestern Russia. Here, we study a 1,500-year time transect of 30 ancient genomes and stable isotope values from the Suzdal region in the Volga-Oka interfluve. We describe a previously un-sampled local Iron Age population and a gradual genetic turnover in the following centuries. Our time transect captures the population shift associated with the spread of Slavic languages and illustrates the ethnically mixed state of medieval Suzdal principality, eventually leading to the formation of the admixed but fully Slavic-speaking population that inhabits the area today. We also observe genetic outliers that highlight the importance of the Suzdal region in medieval times as a hub of long-reaching contacts via trade and warfare.